Amphetamine Derivatives as Monoamine Oxidase Inhibitors - Reyes-Parada, Miguel; Iturriaga-Vasquez, Patricio; Cassels, Bruce K. (Frontiers in Pharmacology, 2020)
Amphetamine and its derivatives exhibit a wide range of pharmacological activities, including psychostimulant, hallucinogenic, entactogenic, anorectic or antidepressant effects. The mechanisms of action underlying these effects are usually related to the ability of the different amphetamines to interact with diverse monoamine transporters or receptors. Moreover, many of these compounds are also potent and selective monoamine oxidase inhibitors. In the present work, we review how structural modifications on the aromatic ring, the amino group and/or the aliphatic side chain of the parent scaffold, modulate the enzyme inhibitory properties of hundreds of amphetamine derivatives. Furthermore, we discuss how monoamine oxidase inhibition might influence the pharmacology of these compounds.